Clinical management of highly resorbed mandibular ridge without fibrous tissue - Veeramalai N Devaki; Paramasivam Manonmani; Kandasamy Balu; Ramraj Jayabalan Aravind (Wolters Kluwer Medknow Publications, 2012)
Alveolar ridge atrophy poses a clinical challenge toward the fabrication of successful prosthesis. Resorption of mandibular denture bearing areas results in unstable non-retentive dentures associated with pain and discomfort. This article describes rehabilitation procedure of a patient with resorbed ridge with maximal areas of coverage to improve support and neutral zone arrangement of teeth to improve stability of denture.